Community natural resource management: the case of woodlots in northern Ethiopia - Gebremedhin, Berhanu; Pender, John L.; Tesfaye, Girmay (International Food Policy Research Institute, 2000)
This paper examines the nature of community management of woodlots and investigates the determinants of collective action and its effectiveness in managing woodlots, based on a survey of 100 villages in Tigray, northern Ethiopia. We find that collective management of woodlots generally functions well in Tigray. Despite limited current benefits received by community members, the woodlots contribute substantially to community wealth, increasing members’ willingness to provide collective effort to manage the woodlots. We find that benefits are greater and problems less on woodlots managed at the village level than those managed at a higher municipality level, and that the average intensity of management is greater on village-managed woodlots. Nevertheless, we find little evidence of differences in collective management of woodlots or its effectiveness on village vs. municipality-managed woodlots, after controlling for other factors. The factors that do significantly affect collective action include population density (higher collective labor input and lower planting density at intermediate than at low or high density), market access (less labor input, planting density and tree survival where market access is better), and presence of external organizations promoting the woodlot (reduces local effort to protect the woodlot and tree survival). The negative effect of market access suggests that higher opportunity costs of labor and/or increased “exit options” undermine collective resource management. The findings suggest collective action may be more beneficial and more effective when managed at a more local level, when the role of external organizations is more demand-driven, and when promoted in intermediate population density communities more remote from markets. In higher population density settings and areas closer to markets, private-oriented approaches are likely to be more effective.